Hepatocellular Adenoma: A Life-Threatening Presentation of a Rare Liver Tumor - Case Report and Literature Review - Lopes,Sara Ramos (2024)
Abstract Hepatocellular adenoma is a rare benign liver tumor that occurs predominantly in young women who use exogenous estrogens. We describe a case of a 40-year-old woman on birth control pill who presented with acute right hypochondrial pain and signs of hemodynamical instability triggered by a large bleeding tumor in the right liver lobe. Arterial embolization was performed with cessation of bleeding. To determine etiology, magnetic resonance imaging was conducted with ﬁndings suggestive of a hepatocellular adenoma. The tumor was surgically resected, and histologic examination made the deﬁnite diagnosis of an inﬂammatory hepatocellular adenoma. This is a noteworthy case of a rare but potentially fatal complication of liver tumors, whose diagnosis requires a high index of suspicion. Clinicians should consider this diagnosis in young women on oral contraceptive pills who present with severe unexplained abdominal pain and hemodynamical instability. This case aimed to raise awareness of this condition, while reviewing important aspects concerning the management of hepatocellular adenomas.